Online help desk system using expert system / Nor Faezan Amdan - Amdan, Nor Faezan (2007)
This research is about to develop an online help desk system with a troubleshooting that uses a rule-based expert system. The main focus for this research is to let user to be able to interact with the system independently to search for solution for problems encountered by them without having to wait for the engineers to consult them. The objectives of this research are to identify the characteristics of online help desk system using rule-based expert system, to design an online help desk system using rule-based expert system and to demonstrate a prototype of an online help desk system. A few prototypes and studies on troubleshooting using rule-based expert system has been chosen through the Internet in order to identify the characteristics of a rule-based expert system by analyzing what are the common characteristics that each of them have. The help desk system is then designed based on the characteristics found. The design and implementation of the help desk system is using PHP language and database used is Oracle 9i. The final product of this research is a prototype of an online help desk system using rule-based expert system. And by that therefore, all three objectives of this research have been achieved.